2007
DOI: 10.1007/s00405-007-0313-1
|View full text |Cite
|
Sign up to set email alerts
|

Voice in early glottic cancer compared to benign voice pathology

Abstract: The purpose of this study is to compare (Dutch) Voice Handicap Index (VHIvumc) scores from a selected group of patients with voice problems after treatment for early glottic cancer with patients with benign voice disorders and subjects from the normal population. The study included a group of 35 patients with voice problems after treatment for early glottic cancer and a group of 197 patients with benign voice disorders. Furthermore, VHI scores were collected from 123 subjects randomly chosen from the normal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 26 publications
(38 reference statements)
4
63
2
Order By: Relevance
“…Recent studies revealed equivalence of various European translations and the original American VHI and confirmed the validity of a Dutch translation of the VHI in Dutch. 32,33 In the previous study, we confirmed that the VHI is an adequate tool for baseline and effectiveness measurement of voice problems in daily life. Regarding clinical relevant difference scores, a difference score of 10 points was found to be useful for individuals in clinical practice and 15 points to be useful in study group designs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recent studies revealed equivalence of various European translations and the original American VHI and confirmed the validity of a Dutch translation of the VHI in Dutch. 32,33 In the previous study, we confirmed that the VHI is an adequate tool for baseline and effectiveness measurement of voice problems in daily life. Regarding clinical relevant difference scores, a difference score of 10 points was found to be useful for individuals in clinical practice and 15 points to be useful in study group designs.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding clinical relevant difference scores, a difference score of 10 points was found to be useful for individuals in clinical practice and 15 points to be useful in study group designs. 33 Applied to the results of this former study, we see that immediately after completion of voice therapy in 7 of the 12 patients, the improvement on the VHI was clinically relevant with an amelioration of more than 10 points. Two of them even managed to obtain a VHI score well within the normal range (below 15) immediately after completion of voice therapy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These authors considered this level to be clinically relevant and useful for distinguishing patients with voice disorders from controls. Their conclusion differs only slightly from the one drawn by Van Gogh et al [17] , who postulated that the level of 15 points should indicate the borderline of the VHI test.…”
Section: Discussioncontrasting
confidence: 54%
“…According to a study by Van Gogh et al [28] , differences regarding VHI scores in group comparisons should be more than 15 points to be statistically and clinically relevant. In the present study no significant VHI differences were found between the age groups, or between groups that differed with respect to the postoperative period.…”
Section: Voice Handicap Indexmentioning
confidence: 99%